The efficiency of star formation in clustered and distributed regions - Bonnell, Ian; Smith, Rowan J.; Clark, Paul C.; Bate, Matthew R. (Monthly notices of the Royal Astronomical Society, 2011)
We investigate the formation of both clustered and distributed populations of young stars in a single molecular cloud. We present a numerical simulation of a 104 M⊙ elongated, turbulent, molecular cloud and the formation of over 2500 stars. The stars form both in stellar clusters and in a distributed mode, which is determined by the local gravitational binding of the cloud. A density gradient along the major axis of the cloud produces bound regions that form stellar clusters and unbound regions that form a more distributed population. The initial mass function (IMF) also depends on the local gravitational binding of the cloud with bound regions forming full IMFs whereas in the unbound, distributed regions the stellar masses cluster around the local Jeans mass and lack both the high-mass and the low-mass stars. The overall efficiency of star formation is ≈ 15 per cent in the cloud when the calculation is terminated, but varies from less than 1 per cent in the regions of distributed star formation to ≈ 40 per cent in regions containing large stellar clusters. Considering that large-scale surveys are likely to catch clouds at all evolutionary stages, estimates of the (time-averaged) star formation efficiency (SFE) for the giant molecular cloud reported here is only ≈ 4 per cent. This would lead to the erroneous conclusion of slow star formation when in fact it is occurring on a dynamical time-scale.